Recent Advances of Shell Matrix Proteins and Cellular Orchestration in Marine Molluscan Shell Biomineralization - Song, Xiaorui; Liu, Zhaoqun; Wang, Lingling; Song, Linsheng (Frontiers in Marine Science, 2019)
Biomineralization refers to the dynamic physiological processes whereby living organisms elaborate mineralized tissues. The existence of extremely abundant molluscan species implies the diversity of mineralized tissues, since the majority of them (Conchifera) produce shells that vary in size and shape. Over the past decades, great progress has been made on the study of the cellular biology of shell biomineralization. The construction of the molluscan shell is the archetype of a biologically controlled mineralization which requires specialized cellular machinery. It has been so far demonstrated that the cells involved in shell formation come from two different tissues: 1) outer mantle epithelial cells (OME) secrete the organic matrix, among which shell matrix proteins (SMPs) determine mineralogical and crystallographic properties of shell; and 2) circulating hemocytes which take part in the deposition of intracellular biominerals and deliver them to the mineralization sites. Mounts of novel SMPs have been identified by using molecular biology techniques (gene cloning, in situ hybridization, immunohistochemistry et al.) coupled with high-throughput sequencing data (genome, proteome, secretome and transcriptome) , and their corresponding functions during shell formation have also been confirmed. The cellular activity of OME and hemocytes during shell formation are significantly increased during shell regeneration process. A potential cellular basis model for molluscan shell formation is proposed. The shell matrix proteins, mostly secreted from OME, and a few secreted from hemocytes or other organs, are either directly delivered to the mineralization site via exosome or classical secretory pathway, or firstly transported to the hemolymph, and then engulfed by hemocytes (mainly granulocytes), which will disintegrate and release shell proteins and CaCO3 crystals at mineralization front. Besides, OME and hemocytes may be involved in the nucleation and remodeling process of CaCO3 mineralization. These cells and cell products work co-operatively to produce an organo-mineral shell, which is composed of various biomineral ultra-structures and macromolecular organic components.